2008
DOI: 10.1021/jp073897w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ions on a Dipalmitoyl Phosphatidylcholine Bilayer. A Molecular Dynamics Simulation Study

Abstract: The effect of physiological concentrations of different chlorides on the structure of a dipalmitoyl phosphatidylcholine (DPPC) bilayer has been investigated through atomistic molecular dynamics simulations. These calculations provide support to the concept that Li+, Na+, Ca2+, Mg2+, Sr2+, Ba2+, and Ac3+, but not K+, bind to the lipid-head oxygens. Ion binding exhibits an influence on lipid order, area per lipid, orientation of the lipid head dipole, the charge distribution in the system, and therefore the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
210
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(248 citation statements)
references
References 67 publications
37
210
1
Order By: Relevance
“…In particular, it has been demonstrated that cations (e.g., Na + ions) are able to penetrate rather deep in the lipid headgroup region. This effect has been observed in zwitterionic, 33,42,46,[50][51][52][53] anionic, 55,56,58 and slightly cationic 61 lipid bilayers. The findings agree with experimental data.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In particular, it has been demonstrated that cations (e.g., Na + ions) are able to penetrate rather deep in the lipid headgroup region. This effect has been observed in zwitterionic, 33,42,46,[50][51][52][53] anionic, 55,56,58 and slightly cationic 61 lipid bilayers. The findings agree with experimental data.…”
Section: Introductionmentioning
confidence: 73%
“…43,45,57 In contrast, using the "Berger lipids", i.e., variants of united-atom force-fields based on refs 70, 96, and 97, tight binding of Na + ions to the lipid carbonyl oxygens is found. 33,42,46,[50][51][52][53]55,56,58,61 Due to the different nature of these two force-fields, simulations using CHARMM27 lipids need to be performed with the area of the bilayer fixed, whereas Berger lipids allow simulations in the NpT ensemble, such that the bilayer can adjust its area to agree with the thermodynamic parameters. Furthermore, the carbonyl region of lipid molecules is more polar in the case of the Berger force-field, so that it attracts cations considerably stronger compared to its CHARMM counterpart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At sub-molar NaCl concentrations, the rotational and translational dynamics of membraneembedded fluorescent probes decreased 7,9,12 , and atomic force microscopy (AFM) experiments showed changes in bilayer hard-ness [14][15][16][17][18] ; in atomistic molecular dynamics (MD) simulations, phospholipid bilayers consistently bound Na + , although the binding strength depended on the model used 12,13,[21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the lack of significant positive electrophoretic mobility of phosphatidylcholine (PC) vesicles in the presence of NaCl (again in contrast to multivalent ions and Li + ) suggested weak binding of Na + 1,8,14,15,27 ; however, these data were also explained by a countering effect of the Cl − ions 22,28 . Furthermore, to reduce the area per lipid in scattering experiments, molar concentrations of NaCl were required 10 , indicating weak ion-lipid interaction; in MD simulations, however, already orders of magnitude lower concentrations resulted in Na + binding and a clear reduction of area per lipid 12,23 . Finally, lipid lateral diffusion was unaltered by NaCl in noninvasive NMR experiments 11 ; however, as it was reduced upon Na + binding in simulations, the reduced lateral diffusion of fluorescent probes 7,9,12 has been interpreted to support the post-2000 'strong binding' view.…”
Section: Introductionmentioning
confidence: 99%